Identifying temperature breaks in the initial stages of the cold chain for Clementines and Navel oranges : a Western Cape case - Conradie, Christoff Anton (Stellenbosch : Stellenbosch University, 2019)
Thesis (MCom)--Stellenbosch University, 2019.